(untitled) (Journal of the College of Education for Women, 2025)
The term Hijabphobia is one of the forms of discourse that is founded on painful racial and religious discrimination against women who wear hijab, and it has received the attention of researchers, scholars, and poets. The study is centered on tracing the notion and its effects according to the theory of the German philosopher Wilhelm Dilthey in Hermeneutics, where the poems are selected from the collection of the poet Mohja Kahf’s E-mails from Scheherazad. In addition to emphasizing the fact that women who wear hijab have a right to do so, this mission merits investigating potential explanations for this discourse and pinpointing potential causes. This paper will help to shed light on the systematic discourse that is directed against hijab.